Exploring Diabetes Wellbeing: A Panel Data Analysis of Physical Activity, Depressive Symptoms, and Health-Related Quality of Life in Korea - Djoko Priyono; Ju Hye Jin; Min-Song Kim; Ainun Najib Febrya Rahman; Haryati Septiani (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2026)
Background: Negative health outcome is the result of both physical activity and depressive symptoms aggravating each other. The potential impact of the interaction between physical activity and depressive symptoms on health-related quality of life is not well understood. This study was conducted to investigate the association between physical activity, depressive symptoms, and health-related quality of life in diabetic patients in Korea. Methods: Data was collected from 1,472 participants with diabetes mellitus from the Korea Health Panel Survey (KHPS) in 2020 after missing values were excluded. Sociodemographic characteristics, physical activity, depressive symptoms, and EQ -5D scores were obtained from the KHPS. To determine the association between physical activity, depressive symptoms, and health-related quality of life, linear regression analysis was performed after controlling for confounding variables. Results: Results showed that physical activity and depressive symptoms had a significant impact on health-related quality of life. After adjustment for gender, age, occupation, and alcohol consumption, physical activity and depressive symptoms remained strongly associated. The incidence of depressive symptoms was 0.74 higher with irregular physical activity than among those who took part in regular physical activity (p < 0.05). Conclusion: Physical activity and depression symptoms are correlated with health-related quality of life. Physical activity intensity and depressive symptoms should be considered when developing programs to improve health-related quality of life.